A Si-containing high entropy alloy material resistant to molten chloride corrosion and a preparation method thereof

The Si-containing high-entropy alloy material prepared by vacuum induction smelting and heat treatment processes solves the problem of insufficient corrosion resistance of traditional materials at high temperatures, and achieves low cost and excellent performance anti-corrosion effect. It is suitable for Next generation CSP power station heat exchange pipe materials.

CN118854137BActive Publication Date: 2024-12-27NANTONG INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411350374.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

In the prior art, traditional Cr-containing ferritic steel and high Mo nickel-based alloy materials have insufficient corrosion performance on molten chloride salt at high temperatures, and are relatively high in cost, making it difficult to meet the next generation of centralized solar photothermal power generation (CSP) power stations. Heat exchange tube material requirements.

Method used

The high-entropy alloy materials containing Si are prepared by vacuum induction smelting technology, with the main components of Co, Cr, Ni, Al, Ti and Si. Through hot forging, hot rolling and annealing treatment processes, an alloy material with excellent corrosion resistance against molten chloride salt is formed. .

Benefits of technology

The prepared Si-containing high-entropy alloy material is low in cost and can form a continuous SiO2 film in a molten chloride environment at 700 ℃, significantly improving the corrosion resistance of molten chloride, excellent mechanical properties, greatly improving safety and corrosion resistance. It is suitable for the following First-generation CSP power station heat exchange pipe material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854137B_ABST
    Figure CN118854137B_ABST
Patent Text Reader

Abstract

This invention discloses a Si-containing high-entropy alloy material resistant to molten chloride corrosion and its preparation method, relating to the technical field of Si-containing high-entropy alloy materials. Its main components are composed of the following atomic percentages: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, with the remainder being Fe and unavoidable impurities. This invention utilizes the CoCrFeNiAl... 0.5 Ti 0.5 By adding an appropriate proportion of Si to a high-entropy alloy and then using a vacuum induction melting process, a Si-containing high-entropy alloy with strong resistance to molten chloride salts and excellent mechanical properties can be prepared. Compared with existing alloy materials, the Si-containing high-entropy alloy material of this invention has better resistance to molten chloride salt corrosion, lower material cost, higher high-temperature structural stability, and is easier to process and apply.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of Si-containing high-entropy alloy materials, and in particular to a Si-containing high-entropy alloy material resistant to molten chloride corrosion and a preparation method thereof. Background Art

[0002] Concentrated solar power (CSP) technology combined with thermal energy storage (hereinafter referred to as heat storage) can efficiently utilize abundant but intermittent solar energy to provide people with stable, dispatchable and low-cost electricity. It is one of the most promising renewable energy technologies in the world.

[0003] At present, commercial CSP power plants mainly use nitrates (such as NaNO3 / KNO3) with high thermal stability and low corrosiveness as heat storage / thermal conductive materials. However, above 565 °C, nitrate ions will decompose into nitrite ions and oxygen at a high rate, which limits its application at higher temperatures. In order to improve thermoelectric efficiency and reduce power generation costs, the operating temperature of the next generation of CSP power plants may exceed 700 °C. Compared with nitrate mixed salts and carbonate mixed salts, chloride mixed salts are cheaper, and at the same time have higher thermal stability and excellent thermophysical properties, making them the most promising candidate salts for the next generation of CSP power plants.

[0004] However, molten chloride salts are extremely corrosive, and traditional Cr-containing ferritic steels have poor resistance to molten chloride salt corrosion and cannot meet the requirements for the use of heat exchanger tube materials for the next generation of CSP power plants. Although high-Mo nickel-based alloys have good resistance to high-temperature molten chloride salt corrosion, they contain a large amount of expensive Mo elements, resulting in high material costs. Therefore, there is an urgent need to develop alloy materials for heat exchanger tubes in the next generation of CSP power plants that have low costs, good high-temperature structural stability, and strong resistance to molten chloride salt corrosion. Summary of the invention

[0005] The object of the present invention is to provide a Si-containing high entropy alloy material resistant to molten chloride corrosion and a preparation method thereof, so as to solve the problems raised in the above background technology.

[0006] To achieve the above-mentioned object, the present invention provides the following technical solution: a Si-containing high-entropy alloy material resistant to molten chloride corrosion, wherein the main components are composed of the following atomic percentages: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and unavoidable impurities.

[0007] Preferably, its components are composed according to the following atomic percentages: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and inevitable impurities.

[0008] A method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion comprises the following steps:

[0009] S1. Using vacuum induction melting process, when mixing raw materials, the main raw material components are mixed according to the following atomic percentage (%) composition: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and unavoidable impurities. All the raw materials weighed after mixing are subjected to vacuum induction melting to obtain an alloy melt;

[0010] S2. The alloy melt prepared in step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling and annealing heat treatment processes in sequence to finally obtain a Si-containing high-entropy alloy material rod or plate resistant to molten chloride corrosion.

[0011] Preferably, in step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and unavoidable impurities.

[0012] Preferably, in step S1, the weighed raw materials are mixed after batching, heated to 1500°C-1600°C at a heating rate of not less than 10°C / min, and melted at the temperature for at least 10 min, and a vacuum induction melting process is used to obtain an alloy melt.

[0013] Preferably, in the step S2, the alloy melt prepared in the step S1 is cast and the alloy ingot obtained by casting is subjected to hot forging, hot rolling and annealing heat treatment processes in sequence;

[0014] The hot forging temperature is controlled at 1200℃-1250℃, and the hot rolling temperature is controlled at 1150℃-1180℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process.

[0015] Finally, the alloy was annealed at 1050 °C for 30 min and then cooled to room temperature to obtain a Si-containing high entropy alloy material rod or plate resistant to molten chloride corrosion.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] 1. Compared with existing alloy materials, the Si-containing high entropy alloy material resistant to molten chloride corrosion prepared by the present invention has lower cost.

[0018] 2. The Si-containing high entropy alloy material resistant to molten chloride corrosion prepared by the present invention can form a continuous SiO2 film on the alloy surface in a molten chloride corrosion environment. The weight change after 100 hours of corrosion by molten chloride (NaCl-KCl-MgCl2, 33-21.6-45.4 mol%) at 700 °C is ≤ 5 mg / cm 2 The corrosion resistance of molten chloride salt is better than that of traditional Cr-containing ferritic steel (T91, 12CrMoV, etc.) and high-Mo nickel-based alloy materials (Inconel 625, C22, etc.).

[0019] 3. The Si-containing high entropy alloy material resistant to molten chloride corrosion of the present invention has excellent mechanical properties after hot forging, hot rolling and annealing. Its room temperature tensile fracture strength is greater than or equal to 950 MPa, and its fracture elongation is greater than or equal to 25%. It can effectively avoid the defect of easy thermal aging existing in high Mo alloys, and can greatly improve the safety of the alloy during use. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a cross-sectional scan of the alloy material in Example 1 after being corroded by molten chloride salt at 700°C for 100 hours;

[0021] Figure 2 This is a silicon element distribution diagram of the alloy material in Example 1 after being corroded by molten chloride salt at 700°C for 100 hours;

[0022] Figure 3 1 is the oxygen element distribution diagram of the alloy material in Example 1 after being corroded by molten chloride salt at 700°C for 100 hours. DETAILED DESCRIPTION

[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] See also Figures 1 to 3The present invention provides a technical solution: a Si-containing high-entropy alloy material resistant to molten chloride corrosion, wherein the main components are composed of the following atomic percentages: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and unavoidable impurities.

[0025] Preferably, its components are composed according to the following atomic percentages: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and inevitable impurities.

[0026] The functions of each element in the formula are as follows:

[0027] The Co element plays a role in solid solution strengthening, thereby improving the alloy's long-lasting strength and creep resistance. At the same time, Co also reduces the solubility of Al and Ti elements in the matrix, thereby increasing the amount of γ' strengthening phase, and the solid solution temperature of the γ' phase also increases with the addition of Co. In addition, Co can also improve the hot working properties, plasticity and impact toughness of the alloy. The preferred amount of Co in the present invention is 15.0-20.0%.

[0028] Cr element can increase the oxidation resistance and corrosion resistance of the alloy. When the Cr content reaches a critical value (above 15.0%), a continuous, dense and well-adhered Cr2O3 oxide film will form on the alloy surface, which can protect the metal surface from high-temperature oxidation and thermal corrosion caused by O, Cl, etc., and play a protective role against oxidation corrosion of the alloy. However, the increase in Cr content is bound to enhance the precipitation tendency of the Cr-rich body-centered α-Cr phase in the alloy. The preferred amount of Cr in the present invention is 15.0-20.0%.

[0029] The Fe element can not only improve the processing performance of the alloy but also reduce the material cost. In the present invention, the preferred amount of Fe is 15.0-20.0%.

[0030] The Ni element has high chemical stability and is almost not oxidized below 500 ºC. It can dissolve a variety of alloy elements without forming harmful phases. The preferred amount of Ni is 15.0-20.0%.

[0031] Al and Ti elements are the main elements that form the γ′ phase. Increasing the total amount of Al and Ti can significantly increase the solid solution temperature and volume fraction of the γ′ phase, and improve the mechanical properties of the alloy. As the Al and Ti content increases, the size of the γ′ phase gradually increases, and the γ′ phase morphology changes from spherical to cubic and then to irregular shape. Ti is also an MC-type carbide-forming element, forming a relatively stable TiC carbide, which delays or even prevents the carbide reaction at high temperatures, thereby stabilizing the Cr in the matrix and indirectly playing a role in resisting thermal corrosion. High Al is beneficial to improving the high-temperature oxidation resistance of the alloy. The preferred Al and Ti element dosages of the present invention are 8.0-10.5%, respectively.

[0032] The addition of Si element can promote the formation of SiO2 passivation layer on the alloy surface, hindering the dissolution of metal elements in molten chloride salt. When the amount of Si is higher than 1.0%, a Si-rich layer begins to form on the alloy surface, improving the corrosion resistance of the alloy; when the amount of Si is higher than 28.0%, a large-sized brittle Si-rich precipitate phase begins to form in the alloy, affecting the structural stability of the alloy. The preferred amount of Si in the present invention is 5.0-25.0%.

[0033] A method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion comprises the following steps:

[0034] S1. Using vacuum induction melting process, when mixing raw materials, the main raw material components are mixed according to the following atomic percentage (%) composition: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and unavoidable impurities. All the raw materials weighed after mixing are subjected to vacuum induction melting to obtain an alloy melt;

[0035] S2. The alloy melt prepared in step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling and annealing heat treatment processes in sequence to finally obtain a Si-containing high-entropy alloy material rod or plate resistant to molten chloride corrosion.

[0036] Preferably, in step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and unavoidable impurities.

[0037] Preferably, in step S1, the weighed raw materials are mixed after batching, heated to 1500°C-1600°C at a heating rate of not less than 10°C / min, and melted at the temperature for at least 10 min, and a vacuum induction melting process is used to obtain an alloy melt.

[0038] Preferably, in the step S2, the alloy melt prepared in the step S1 is cast and the alloy ingot obtained by casting is subjected to hot forging, hot rolling and annealing heat treatment processes in sequence;

[0039] The hot forging temperature is controlled at 1200℃-1250℃, and the hot rolling temperature is controlled at 1150℃-1180℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process.

[0040] Finally, the alloy was annealed at 1050 °C for 30 min and then cooled to room temperature to obtain a Si-containing high entropy alloy material rod or plate resistant to molten chloride corrosion.

[0041] Embodiment 1:

[0042] In this embodiment, a Si-containing high entropy alloy material resistant to molten chloride corrosion and a preparation method thereof include the following steps:

[0043] S1. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following atomic percentage (%) composition:

[0044] Co 19.0%;

[0045] Cr 19.0%;

[0046] Ni 19.0%;

[0047] Al 9.5%;

[0048] Ti 9.5%;

[0049] Si 5.0%;

[0050] Fe balance;

[0051] The ingredients are mixed with an equal amount of raw materials, and the temperature is raised to 1500°C to 1600°C at a heating rate of not less than 10°C / min, and the temperature is kept for melting for at least 10 minutes, and a vacuum induction melting process is adopted to obtain an alloy melt;

[0052] S2. Cast the alloy melt prepared in step S1, and subject the alloy ingot obtained by casting to hot forging, hot rolling and annealing heat treatment processes in sequence; wherein the hot forging temperature is controlled to be 1200 ℃ ~ 1250 ℃, and the hot rolling temperature is controlled to be 1150 ℃ ~ 1180 ℃. In order to avoid deformation and cracking during hot forging and hot rolling, the alloy ingot will be returned to the furnace for multiple times and then forged / rolled during the hot deformation process. Finally, the alloy is annealed at 1050 ℃ for 30 min and then cooled to room temperature to obtain a Si-containing high entropy alloy sheet resistant to molten chloride corrosion.

[0053] After experimental testing, the test results show that the room temperature tensile fracture strength of the plate of Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment is 960 MPa, the fracture elongation is 38%, and the weight change after 700 ℃ molten chloride corrosion for 100 hours is 4.8 mg / cm 2 .

[0054] Attached Figure 1-3 This is a cross-sectional scan of the alloy material in Case 1 after being corroded by molten chloride salt at 700 ℃ for 100 hours. It can be seen from the figure that a continuous SiO2 film is formed on the surface of the alloy during the molten chloride salt corrosion process. The formation of the continuous SiO2 film can hinder the progress of high-temperature molten chlorine corrosion and improve the corrosion resistance of the alloy.

[0055] The Si-containing high-entropy alloy material resistant to molten chloride corrosion prepared in this embodiment has excellent mechanical properties, and its molten chloride corrosion resistance is better than that of traditional Cr-containing ferritic steel or high-Mo nickel-based alloy materials. It can be used as a next-generation CSP power station heat exchange tube material and other components. It is the best candidate material to replace traditional Cr-containing ferritic steel or expensive high-Mo nickel-based materials in the future, and can greatly improve the molten chloride corrosion resistance and safety.

[0056] Embodiment 2:

[0057] This embodiment is basically the same as the first embodiment, except that:

[0058] In this embodiment, a method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion with excellent mechanical properties comprises the following steps:

[0059] S1. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following mass percentage (%):

[0060] Co 18.0%;

[0061] Cr 18.0%;

[0062] Ni 18.0%;

[0063] Al 9.0%;

[0064] Ti 9.0%;

[0065] Si 10.0%;

[0066] Fe balance;

[0067] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;

[0068] S2. This step is the same as that in Example 1.

[0069] After experimental testing, the test results show that the room temperature tensile fracture strength of the plate of Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment is 980 MPa, the fracture elongation is 31%, and the weight change after 700 ℃ molten chloride corrosion for 100 hours is 4.3 mg / cm 2 , a continuous SiO2 film is formed on the alloy surface during the molten chloride corrosion process. The Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment has excellent mechanical properties, and its molten chloride corrosion resistance is better than that of traditional Cr-containing ferritic steel or high-Mo nickel-based alloy materials, and can be used as the next generation of CSP power station heat exchange tube materials and other parts. It is the best candidate material to replace traditional Cr-containing ferritic steel or expensive high-Mo nickel-based materials in the future, and can greatly improve the molten chloride corrosion resistance and safety.

[0070] Embodiment three:

[0071] This embodiment is basically the same as the above embodiment, with the following features:

[0072] In this embodiment, a method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion with excellent mechanical properties comprises the following steps:

[0073] S1. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following mass percentage (%):

[0074] Co 17.0%;

[0075] Cr 17.0%;

[0076] Ni 17.0%;

[0077] Al 8.5%;

[0078] Ti 8.5%;

[0079] Si 15.0%;

[0080] Fe balance;

[0081] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;

[0082] S2. This step is the same as that in Example 1.

[0083] After experimental testing, the test results show that the room temperature tensile fracture strength of the plate of Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment is 1050 MPa, the fracture elongation is 28%, and the weight change after 700 ℃ molten chloride corrosion for 100 hours is 3.2 mg / cm 2 , a continuous SiO2 film is formed on the alloy surface during the molten chloride corrosion process. The Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment has excellent mechanical properties, and its molten chloride corrosion resistance is better than that of traditional Cr-containing ferritic steel or high-Mo nickel-based alloy materials, and can be used as the next generation of CSP power station heat exchange tube materials and other parts. It is the best candidate material to replace traditional Cr-containing ferritic steel or expensive high-Mo nickel-based materials in the future, and can greatly improve the molten chloride corrosion resistance and safety.

[0084] Embodiment 4:

[0085] This embodiment is basically the same as the above embodiment, with the following features:

[0086] In this embodiment, a method for preparing a Si-containing high entropy alloy material resistant to molten chloride corrosion with excellent mechanical properties comprises the following steps:

[0087] S1. Using vacuum induction melting process, when mixing raw materials, the raw material components used are mixed according to the following mass percentage (%):

[0088] Co 16.0%;

[0089] Cr 16.0%;

[0090] Ni 16.0%;

[0091] Al 8.0%;

[0092] Ti 8.0%;

[0093] Si 20.0%;

[0094] Fe balance;

[0095] All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt;

[0096] S2. This step is the same as that in Example 1.

[0097] After experimental testing, the test results show that the room temperature tensile fracture strength of the plate of Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment is 1080 MPa, the fracture elongation is 26%, and the weight change after 700 ℃ molten chloride corrosion for 100 hours is 2.9 mg / cm 2 , a continuous SiO2 film is formed on the alloy surface during the molten chloride corrosion process. The Si-containing high entropy alloy material resistant to molten chloride corrosion prepared in this embodiment has excellent mechanical properties, and its molten chloride corrosion resistance is better than that of traditional Cr-containing ferritic steel or high-Mo nickel-based alloy materials, and can be used as the next generation of CSP power station heat exchange tube materials and other parts. It is the best candidate material to replace traditional Cr-containing ferritic steel or expensive high-Mo nickel-based materials in the future, and can greatly improve the molten chloride corrosion resistance and safety.

[0098] In summary, the Si-containing high-entropy alloy material resistant to high-temperature molten chloride corrosion in the above-mentioned embodiment has excellent mechanical properties and resistance to high-temperature molten chloride corrosion, and its main components are composed according to the following atomic percentage (%): Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1-30%, and the remaining components are Fe and inevitable impurities. After batching and vacuum induction melting, casting molding, and then hot forging, hot rolling and annealing treatment, an alloy material bar or plate with excellent mechanical properties and resistance to high-temperature chloride ion molten salt corrosion is finally obtained. The alloy material resistant to high-temperature chloride ion molten salt corrosion of the present invention has the advantages of good strength and plasticity, high organizational stability, low cost, excellent resistance to chloride ion corrosion and hot processing formability.

[0099] It is known from common technical knowledge that the present invention can be implemented by other embodiments that do not deviate from its spirit or essential features. Therefore, the above disclosed embodiments are only illustrative in all respects and are not exclusive. All changes within the scope of the present invention or within the scope equivalent to the present invention are included in the present invention.

Claims

1. A Si-containing high entropy alloy material resistant to molten chloride corrosion, characterized in that: Its main components are composed according to the following atomic percentages: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and inevitable impurities; A method for resisting molten chloride salt corrosion of Si-containing high entropy alloy materials comprises the following steps: S1. A vacuum induction melting process is adopted. When the raw materials are batched, the main raw material components are batched according to the following atomic percentage (%) composition: Co: 10.0-30.0%, Cr: 10.0-30.0%, Ni: 10.0-30.0%, Al: 6.5-11.0%, Ti: 6.5-11.0%, Si: 1.0-30.0%, and the remaining components are Fe and inevitable impurities. All the raw materials weighed after batching are subjected to vacuum induction melting to obtain an alloy melt; S2. Casting the alloy melt prepared in step S1, and subjecting the alloy ingot obtained by casting to hot forging, hot rolling and annealing heat treatment processes in sequence, to finally obtain a Si-containing high entropy alloy material bar or plate resistant to molten chloride corrosion; A continuous SiO2 film can be formed on the alloy surface. After 100h corrosion in molten chloride at 700℃, the weight change is ≤ 5 mg / cm 2 , the chloride salt is 33-21.6-45.4 mol% NaCl-KCl-MgCl2; The room temperature tensile strength of the alloy material is greater than or equal to 950 MPa, and the elongation at break is greater than or equal to 25%.

2. The Si-containing high entropy alloy material resistant to molten chloride corrosion according to claim 1, characterized in that: In the step S1, the raw material components are prepared according to the following atomic percentage composition: Co: 15.0-20.0%, Cr: 15.0-20.0%, Ni: 15.0-20.0%, Al: 8.0-10.5%, Ti: 8.0-10.5%, Si: 5.0-25.0%, and the remaining components are Fe and unavoidable impurities.

3. The Si-containing high entropy alloy material resistant to molten chloride corrosion according to claim 1, characterized in that: In the step S1, the weighed raw materials are mixed and heated at a heating rate of not less than 10°C / min to 1500°C-1600°C, and the temperature is kept for melting for at least 10 minutes, and a vacuum induction melting process is used to obtain an alloy melt.

4. The Si-containing high entropy alloy material resistant to molten chloride corrosion according to claim 1, characterized in that: In the step S2, the alloy melt prepared in the step S1 is cast into a mold, and the alloy ingot obtained by casting is subjected to hot forging, hot rolling and annealing heat treatment processes in sequence; The hot forging temperature is controlled at 1200℃-1250℃, and the hot rolling temperature is controlled at 1150℃-1180℃. In order to avoid deformation and cracking during hot forging and hot rolling, the steel will be returned to the furnace for multiple times before forging / rolling during the hot deformation process. Finally, the alloy was annealed at 1050 °C for 30 min and then cooled to room temperature to obtain a Si-containing high entropy alloy material rod or plate resistant to molten chloride corrosion.